2009
DOI: 10.3109/09553000903242099
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces an antitumour immune response to mouse melanoma

Abstract: The present study suggests that neoadjuvant irradiation of cutaneous melanoma tumours prior to surgical resection can stimulate an endogenous anti-melanoma host immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 34 publications
(34 reference statements)
1
47
0
Order By: Relevance
“…Subsequent experiments showed that the immunogenicity of apoptosis critically relies on CRT exposure. Thus, the knockdown of CRT abolishes the immunogenicity of cell death in multiple tumor models (13)(14)(15)(16), whereas the absorbance of recombinant CRT protein to cells that die of nonimmunogenic cell death restores their immunogenicity (17,18). In addition, CRT exposure determines the engulfment of dying tumor cells by specific DC subsets (15), in line with previous studies showing that surface CRT can serve as an "eat me" signal (19).…”
Section: Introductionsupporting
confidence: 69%
“…Subsequent experiments showed that the immunogenicity of apoptosis critically relies on CRT exposure. Thus, the knockdown of CRT abolishes the immunogenicity of cell death in multiple tumor models (13)(14)(15)(16), whereas the absorbance of recombinant CRT protein to cells that die of nonimmunogenic cell death restores their immunogenicity (17,18). In addition, CRT exposure determines the engulfment of dying tumor cells by specific DC subsets (15), in line with previous studies showing that surface CRT can serve as an "eat me" signal (19).…”
Section: Introductionsupporting
confidence: 69%
“…22 It turned out that the unsuspected ability of doxorubicin (an anthracycline employed for the treatment of various carcinomas) to trigger ICD as a standalone intervention, hence converting dying cancer cells into a vaccine that is efficient in the absence of adjuvants, is shared by a relatively restricted set of lethal triggers. [28][29][30][31][32][33] These include, but perhaps are not limited to, mitoxantrone and epirubicin (2 other anthracyclines currently used in the clinic), [34][35][36][37] bleomycin (a glycopeptide antibiotic endowed with antineoplastic properties), 38 oxaliplatin (a platinum derivative generally employed against colorectal carcinoma), [39][40][41][42] cyclophosphamide (an alkylating agent approved for the treatment of neoplastic and autoimmune conditions), [43][44][45][46][47][48] etoposide (a topoisomerase inhibitor currently used for the treatment of several neoplasms) combined with the chemical inhibitor of glycolysis 2-deoxyglucose, 49,50 patupilone (a microtubular inhibitor that has not yet been approved for use in humans), [51][52][53] septacidin (an antifungal antibiotic produced by Streptomyces fibriatus) 54,55 specific forms of radiation therapy, 34,[56][57][58][59][60][61][62][63][64] photodynamic therapy (a clinically approved antican...…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of CRT on the plasma membrane can precede anthracycline-induced apoptosis and is required for cell death to be perceived as immunogenic [225]. Several studies have found translocation of intracellular CRT to the cell surface in response to anthracycline and high doses of irradiation in a variety of human and rodent cancer cells, including melanoma [226][227][228]. Surface CRT then initiates an apoptotic signal [229] which is critical for the recognition and engulfment by DCs.…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 99%